2014
DOI: 10.1097/pec.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Pediatric Hand Fractures and Review of the Literature

Abstract: The pattern of pediatric hand fracture in different age groups is highlighted in this article. The observations from this study will hopefully encourage further review with a larger cohort and a focus on preventative measures for pediatric hand fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
61
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 17 publications
15
61
3
Order By: Relevance
“…The gender differences in the number of hand injuries and fractures in our study is similar to the results of other studies in the literature [ 3 , 5 , 6 , 7 , 9 , 14 , 15 , 16 , 17 ]. The predominance of fractures among males increases with age and is most apparent among teenagers [ 3 , 5 , 6 , 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…The gender differences in the number of hand injuries and fractures in our study is similar to the results of other studies in the literature [ 3 , 5 , 6 , 7 , 9 , 14 , 15 , 16 , 17 ]. The predominance of fractures among males increases with age and is most apparent among teenagers [ 3 , 5 , 6 , 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, compared to older adults, a larger proportion of fractures in children and young adults are related to sports and relatively high impact falls and other injuries [24]. In addition to force of impact, other mechanical factors influence risk for fracture after a fall.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from head injuries, the hand is the most commonly injured part of the body in young children and hand fractures are the leading cause of morbidity in children. 24,25 Literature shows proximal phalanx fractures are the most common type of hand frac tures in children. 8 Furthermore, in a prospective study inves tigating hand injuries in children, Liu et al found that they more common in males, and that the vast majority of injuries were nonsurgical and associated with athletic activities.…”
Section: Discussionmentioning
confidence: 99%